Crystal structure of [tetraaqua-bis((3-carboxy-5-(pyridin-4-yl)benzoate-κ1N)cobalt(II)] tetrahydrate, C26H32CoN2O16 - Bao Xiaobo; Tian Chongchong (Zeitschrift für Kristallographie - New Crystal Structures)
C26H32CoN2O16, orthorhombic, Fdd2 (no. 43), a = 24.8013(10) Å, b = 35.8890(16) Å, c = 6.9911(4) Å, V = 6222.7(5) Å3, Z = 8, Rgt(F) = 0.0487, wRref(F2) = 0.1462, T = 293(2) K.